The Incidence and Mortality of Colorectal Cancer and Its Relationship With the Human Development Index in Asia - Mahshid Ghoncheh; Maryam Mohammadian; Abdollah Mohammadian-Hafshejani; Hamid Salehiniya (Ubiquity Press, 2017)
Background Colorectal cancer is the second most common cancer in women and the third most common cancer among men, and its incidence is increasing in Asia. Awareness about the status of this cancer incidence and mortality is necessary for a better plan. Objectives The present study was done with the aim to investigate the incidence and mortality of colorectal cancer and its relationship with the Human Development Index (HDI) in Asia in 2012. Methods This study was an ecological study, which was conducted based on the GLOBOCAN project of the World Health Organization for Asian countries. We assessed the correlation between standardized incidence rates (SIR) and standardized mortality rates (SMR) of colorectal cancer with HDI and its components using SPSS software, version 18 (SPSS Inc., Chicago, IL). Results A total of 592,563 incidences of and 325,752 deaths from colorectal cancer were recorded in Asian countries in 2012. The 5 countries with the highest SIR were Republic of Korea (45 per 100,000), Israel (35.9 per 100,000), Singapore (33.7 per 100,000), Japan (32.2 per 100,000), and Jordan (25.6 per 100,000). The 5 countries with the highest SMR for colorectal cancer were Jordan (15.5 per 100,000), Kazakhstan (12.8 per 100,000), Democratic Republic of Korea (12 per 100,000), Brunei (12 per 100,000), and Japan (11.9 per 100,000). Correlation between HDI and SIR was 0.709 overall ('P' ≤ .001)- 0.667 in men ('P' ≤ .001) and 0.759 in women ('P' ≤ .001). Also, correlation between HDI and SMR overall was 0.517 ('P' ≤ .001)- 0.447 in men ('P' = .002) and 0.593 in women ('P' ≤ .001). Conclusions Cancer incidence and mortality are higher in countries with more development. A positive and statistically significant correlation was found between standardized incidence and mortality rate of colorectal cancer and the Human Development Index and its components.